Positive electrode active material, battery, and method for producing positive electrode active material

By using the material composed of LixNiaCobMncMdO2 in the positive electrode active material of the battery and fully dispersed and added elements inside the particles, the problem of battery resistance rising after cycling is solved, and the circulation characteristics of the battery are significantly improved.

CN119890283APending Publication Date: 2025-04-25TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411489411.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

After repeated cycles of charge and discharge, the battery resistance is prone to rise, affecting the cycle characteristics of the battery.

Method used

The positive electrode active material represented by LixNiaCobMncMdO2 has a M element bias ratio of 1.0% or more. By fully dispersing and adding elements inside the particles of the positive electrode active material, the stability of the layered structure is improved, and the movement of Li ions and cation mixing are inhibited.

Benefits of technology

It effectively suppresses the battery's resistance rise after the charge and discharge cycle, and improves the battery's cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890283A_ABST
    Figure CN119890283A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode active material, a battery, and a method for manufacturing the positive electrode active material. Provided is a positive electrode active material capable of improving cycle characteristics when used in a battery. A positive electrode active material having a composition represented by LixNiaCobMncMdO2, in which, in a TEM-EDX image of a cross-section of a particle of the positive electrode active material, when an inner region extending from the center of the particle to 70% of the radius is divided into a region of 10 nm square, the proportion of a region in which the concentration of an element represented by M is 10% by mass or more is 1.0% or more with respect to the entire region. Further, in the composition, 0.1 < = x < = 1.5, 0.5 < = a < = 1.0, 0 < = b < = 0.3, 0 < = c < = 0.3, a + b + c = 1.0, 0.0005 < = d < = 0.05, and M represents at least one element selected from the group consisting of Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh, and Zr.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material, a battery, and a method for producing the positive electrode active material. Background Art

[0002] Conventionally, various additive elements have been added to positive electrode active materials used in batteries for the purpose of improving the resistance characteristics of the batteries.

[0003] For example, Patent Document 1 discloses transition metal composite hydroxide particles, which contain nickel (Ni), manganese (Mn), cobalt (Co) and element A (A) in a ratio expressed by mass ratio of Ni:Mn:Co:A=x:y:z:t (x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<t≤0.1, and the element A is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, La, Hf, Ta, and W), and have a central portion including primary particles, and an outer shell portion arranged outside the central portion and the primary particles are arranged more closely than the central portion, and the abundance ratio (th) of the element A in the central portion is smaller than the abundance ratio (ts) of the element A in the outer shell portion.

[0004] In addition, Patent Document 2 discloses a surface-modified lithium-containing composite oxide for a positive electrode of a lithium-ion secondary battery, wherein the composite oxide has a general formula (Li 1+x (Co (1-a-b-m) Ni a Al b M m ) 1-x O 2-(f / 2) F f ) is modified with a surface modification compound containing at least one element selected from group S1 and group S2, group S1 is a group consisting of Al, Zr, Ti, Mg, Zn, Nb, Mo, Ta, W and rare earth, group S2 is a group consisting of F, P and S, M is a transition metal other than Co and Ni, Sn, Ge, Na, K, B, C, Si, P, S, Zn, Ga, Bi, an element of the second group and at least one element of rare earth, and is -0.05≤x≤0.05, 0<a≤0.25, 0<b≤0.05, 0≤m≤0.04, 0≤f≤0.05.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-147314

[0008] Patent Document 2: Japanese Patent No. 6359323 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In batteries having a conventionally used positive electrode active material, the battery resistance may increase after repeated charge and discharge cycles. It is desired to suppress the increase in battery resistance even after the charge and discharge cycles, that is, to improve the cycle characteristics.

[0011] The present disclosure has been made in view of the above-mentioned actual situation, and an object of the present disclosure is to provide a positive electrode active material capable of improving cycle characteristics when used in a battery, a battery including the positive electrode active material, and a method for producing the positive electrode active material.

[0012] Means for solving problems

[0013] Means for solving the above-mentioned problems include the following.

[0014] <1> The positive electrode active material has Li x Ni a Co b Mn c M d O2 represents a composition, for the TEM-EDX image of the cross section of the particle of the positive electrode active material, when the inner area from the center of the particle to 70% of the radius is divided into 10nm square areas, the proportion of the area in which the concentration of the element represented by M is 10 mass% or more is 1.0% or more relative to the whole area, and in the composition, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, 0.0005≤d≤0.05, and M represents at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh and Zr.

[0015] <2> The positive electrode active material according to <1>, wherein the element represented by M is at least one element selected from the group consisting of Ta, Al, Ba, Pr, and La.

[0016] <3> The positive electrode active material according to <2>, wherein the element represented by M is La.

[0017] <4> The positive electrode active material according to any one of <1> to <3>, wherein the ratio of the region in which the concentration of the element represented by M is 10 mass % or more is 3.0% or more relative to the entire region.

[0018] <5> A battery comprising the positive electrode active material according to any one of <1> to <4>.

[0019] <6> A method for producing a positive electrode active material, comprising:

[0020] A step of preparing a solution A in which a raw material containing an element represented by M is dissolved;

[0021] A step of preparing a solution B in which raw materials respectively containing Ni, Co and Mn are dissolved;

[0022] A step of adding the solution A to an alkaline solution to precipitate hydroxide;

[0023] A step of adding the solution B to the alkaline solution in which the hydroxide is precipitated to cause precipitation;

[0024] A step of collecting a precipitate from the alkaline solution;

[0025] a step of mixing the precipitate with a raw material containing Li to obtain a mixture; and

[0026] The step of calcining the mixture,

[0027] Wherein, M represents at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh and Zr.

[0028] Effects of the Invention

[0029] According to the present disclosure, there are provided a positive electrode active material capable of improving cycle characteristics when used in a battery, a battery including the positive electrode active material, and a method for producing the positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic cross-sectional view for explaining a method for measuring the localization rate of the M element in the positive electrode active material according to an embodiment of the present disclosure.

[0031] Figure 2 It is a schematic cross-sectional view for explaining a method for measuring the localization rate of the M element in the positive electrode active material according to an embodiment of the present disclosure.

[0032] Figure 3 It is a schematic cross-sectional view for explaining a method for producing a positive electrode active material according to an embodiment of the present disclosure.

[0033] Description of Reference Numerals

[0034] 2Positive electrode active material particles

[0035] 4A M element nucleus

[0036] 4B M element particles

[0037] 20 particles DETAILED DESCRIPTION

[0038] Hereinafter, an embodiment as an example of the present disclosure will be described. These descriptions and examples are illustrative of the embodiment and do not limit the scope of the invention.

[0039] In the numerical range recorded in stages in the specification, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this specification, the upper limit or lower limit of its numerical range can be replaced by the value shown in the embodiment.

[0040] Each component may contain a plurality of corresponding substances.

[0041] When referring to the amount of each component in a composition, if there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plurality of substances present in the composition.

[0042] The term "process" refers not only to an independent process but also to a process that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved.

[0043] <Positive electrode active material>

[0044] The positive electrode active material according to the embodiment of the present disclosure has a Li x Ni a Co b Mn c M d The composition represented by O2.

[0045] Moreover, for the TEM-EDX (Transmission Electron Microscope-Energy Di spers ive X-ray Spectroscopy) image of the cross section of the particle of the positive electrode active material, when the inner area from the center of the particle to 70% of the radius is divided into 10 nm square areas, the proportion of the area in which the concentration of the element represented by M is 10 mass % or more (hereinafter also referred to as "M element bias") is 1.0% or more relative to the entire area.

[0046] (In the above composition, 0.1≤x≤1.0, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, 0.0005≤d≤0.05, and M represents at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh, and Zr.)

[0047] So far, in order to improve the resistance characteristics of the battery, etc., an additional element (i.e., the element represented by M, hereinafter also referred to as "M element") is added to the positive electrode active material. In addition, in the past, the additional element (M element) existed partially on the surface of the particles of the positive electrode active material (for example, forming a coating on the surface).

[0048] Furthermore, in batteries using such conventional positive electrode active materials, the battery resistance may increase after repeated charge and discharge cycles. Therefore, it is desired to suppress the increase in battery resistance even after repeated charge and discharge cycles, that is, to improve the cycle characteristics.

[0049] The M element partiality of the positive electrode active material involved in the embodiment of the present disclosure is 1.0% or more, that is, the added element (M element) in the particles of the positive electrode active material is fully dispersed in the internal area and exists. By the presence of the M element in a sufficient amount in the internal area, the stabilization effect of the layered structure is greatly improved, and as a result, the Ni mixing (cation mixing) in the Li layer during charging and discharging in the battery is suppressed, and the movement of Li ions during charging and discharging is suppressed. Thus, the cycle characteristics can be improved in the battery using the positive electrode active material.

[0050] Next, the positive electrode active material according to the embodiment of the present disclosure will be described in detail.

[0051] (composition)

[0052] The positive electrode active material according to the embodiment of the present disclosure has a Li x Ni a Co b Mn c M d The composition represented by O2.

[0053] (In the above composition, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, 0.0005≤d≤0.05, and M is at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh, and Zr.)

[0054] In the composition of the positive electrode active material, from the viewpoint of resistance characteristics in the battery, etc., the ratio x of Li is 0.1 to 1.5, preferably 0.3 to 1.4, and more preferably 0.5 to 1.2.

[0055] The ratio a of Ni is 0.5 or more and 1.0 or less, preferably 0.6 or more and 0.9 or less, and more preferably 0.7 or more and 0.8 or less.

[0056] The ratio b of Co is 0 to 0.3, preferably 0 to 0.2, and more preferably 0.1 to 0.2.

[0057] The ratio c of Mn is 0 to 0.3, preferably 0 to 0.2, and more preferably 0.1 to 0.2.

[0058] In addition, the total ratio (a+b+c) of Ni, Co and Mn is 1.0.

[0059] The positive electrode active material contains at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh and Zr as an additive element (M element). By containing the above-mentioned elements as additive elements, the cycle characteristics in the battery, that is, the suppression degree of the increase of the battery resistance after repeated charge and discharge cycles, can be improved.

[0060] Furthermore, from the viewpoint of further improving the cycle characteristics, the positive electrode active material preferably contains at least one element selected from Ta, Al, Ba, Pr and La as an additional element (M element), and more preferably contains La.

[0061] In the composition of the positive electrode active material, the ratio d of M is 0.0005 or more and 0.05 or less, preferably 0.001 or more and 0.04 or less, and more preferably 0.005 or more and 0.02 or less.

[0062] (M element partiality rate)

[0063] In the positive electrode active material involved in the embodiment of the present disclosure, for the TEM-EDX image of the cross section of the particle of the positive electrode active material, when the inner area from the center of the particle to 70% of the radius is divided into 10 nm square areas, the proportion of the area where the concentration of the element represented by M is 10 mass % or more ("M element bias") is more than 1.0% relative to the entire area.

[0064] The M element localization ratio of 1.0% or more means that the added element (M element) is sufficiently dispersed and present in the inner region of the particles of the positive electrode active material, thereby improving the cycle characteristics of a battery using the positive electrode active material.

[0065] Furthermore, the M element partial ratio is preferably 3.0% or more, more preferably 4.0% or more, from the viewpoint of further improving the cycle characteristics in the battery. On the other hand, the upper limit of the M element partial ratio is not particularly limited, but from the viewpoint of suppressing the amount of the added element (M element), it is preferably 15.0% or less, more preferably 10.0% or less.

[0066] [Determination of the bias rate of M element]

[0067] A method for measuring the localization rate of the M element in the particles of the positive electrode active material will be described.

[0068] First, a TEM-EDX image of a cross section of a particle of a positive electrode active material is taken. Figure 1 . Figure 1 The positive electrode active material particle 2 shown contains particles 4B of the element M inside. In the cross-sectional image of the positive electrode active material particle 2, the inner region from the center to 70% of the radius (i.e., the region from the surface to 30% of the radius is excluded) is shown. Figure 1 The inner area surrounded by the dotted line in the figure is taken as the observation object. Figure 2 The area shown is divided into 10 nm square regions, and the concentration of the M element is measured for each region.

[0069] However, in the division into the inner area ( Figure 1 In the 10 nm square region existing at the end of the area (the inner area surrounded by the dotted line in the figure), there is an area that is not filled with the positive electrode active material particles 2. Therefore, in the area divided into 10 nm squares, the area that is not filled with the positive electrode active material particles 2 is excluded from the object, and only the area whose entire range is filled with the positive electrode active material particles 2 is the object of measurement.

[0070] Then, the ratio of regions where the concentration of the M element is 10 mass % or more in all regions divided into 10 nm squares (excluding regions not filled with positive electrode active material particles 2) is calculated. This ratio is calculated according to the following formula.

[0071] The ratio = the number of regions where the concentration of the M element is 10 mass % or more / the number of all regions divided into 10 nm squares in the inner region (excluding regions not filled with positive electrode active material particles) × 100

[0072] This ratio calculation is performed on 10 cross-sectional images of particles of the positive electrode active material, and the arithmetic mean value is defined as the M element partial ratio.

[0073] <Method for producing positive electrode active material>

[0074] Next, a method for producing a positive electrode active material according to an embodiment of the present disclosure will be described. The positive electrode active material according to the embodiment of the present disclosure described above can be produced by the method for producing a positive electrode active material according to an embodiment of the present disclosure described below.

[0075] The method for producing a positive electrode active material according to an embodiment of the present disclosure includes the following steps (1) to (7).

[0076] (1) A step of preparing a solution A in which a raw material containing an element represented by M is dissolved

[0077] (Wherein, M represents at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh and Zr.)

[0078] (2) Step of preparing a solution B in which raw materials containing Ni, Co, and Mn are dissolved

[0079] (3) Step of adding solution A to the alkaline solution to precipitate the hydroxide

[0080] (4) Step of adding solution B to the alkaline solution in which the hydroxide is precipitated to cause precipitation

[0081] (5) Step of collecting precipitate from alkaline solution

[0082] (6) A step of mixing the precipitate with a raw material containing Li to obtain a mixture

[0083] (7) Step of calcining the mixture

[0084] (1) A step of preparing a solution A in which a raw material containing an element represented by M is dissolved

[0085] First, a solution A is prepared in which a raw material containing an additive element (M element, i.e., at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh and Zr) is dissolved.

[0086] For example, the solution A can be prepared by dissolving a raw material containing the M element in a solvent such as water. The concentration of the solution A is preferably in the range of 5 to 30% by mass, for example.

[0087] As a raw material containing the M element, for example, as a raw material containing Ta, sulfates such as Ta(SO4)2 can be listed, as a raw material containing Al, sulfates such as Al2(SO4)3 can be listed, as a raw material containing Ba, sulfates such as BaSO4 can be listed, as a raw material containing Pr, sulfates such as Pr2(SO4)3 can be listed, as a raw material containing La, sulfates such as La2(SO4)3 can be listed. In addition, as other raw materials containing the M element, generally used raw materials can also be used, for example, sulfates containing each M element can be listed.

[0088] (2) Step of preparing a solution B in which raw materials containing Ni, Co, and Mn are dissolved

[0089] A solution B in which a raw material containing Ni, a raw material containing Co, and a raw material containing Mn are dissolved is prepared.

[0090] For example, a solution B can be prepared by dissolving a raw material containing Ni, a raw material containing Co, and a raw material containing Mn in a solvent such as water. The concentration of the solution B is preferably in the range of 10 to 40 mass %. The ratio of Ni / Co / Mn is preferably 1.0 / 0.8 to 1.2 / 0.8 to 1.2 (atm %) relative to Ni 1.

[0091] Examples of the raw material containing Ni include sulfates such as NiSO 4 , examples of the raw material containing Co include sulfates such as CoSO 4 , and examples of the raw material containing Mn include sulfates such as MnSO 4 .

[0092] (3) Step of adding solution A to the alkaline solution to precipitate the hydroxide

[0093] Next, solution A (a solution in which a raw material including the M element is dissolved) is added to the alkaline solution to precipitate a hydroxide.

[0094] Among them, use Figure 3 The method for producing the positive electrode active material according to the embodiment of the present disclosure is described below. By adding solution A to the alkaline solution, the hydroxide is precipitated, so that Figure 3 As shown in (a) in FIG. 1 , a core 4A of an additive (M element) can be formed.

[0095] In this step, for example, the NH3 aqueous solution is replaced with nitrogen and the pH is adjusted to alkaline, and the solution A is added dropwise while controlling the pH to a certain value (for example, pH 10 to 12), so that the hydroxide (i.e., Figure 3 4A) precipitation of the nuclei with the additions in.

[0096] (4) Step of adding solution B to the alkaline solution in which the hydroxide is precipitated to cause precipitation

[0097] Next, solution B is added to the alkaline solution in which the hydroxide (core 4A of the additive) is precipitated to obtain a precipitate. By further adding solution B to the alkaline solution in which the hydroxide is precipitated, Figure 3 As shown in (b) in FIG. 1 , particles 20 of the hydroxide 2 including Ni, Co, and Mn are crystallized around the core 4A of the additive (M element), and the particles 20 are obtained as a precipitate.

[0098] In this step, for example, the hydroxide-precipitating alkaline solution is further controlled to a certain pH (eg, pH 10 to 12), and then solution B and NH 3 are added dropwise, thereby precipitating the hydroxide of the transition metal.

[0099] (5) Step of collecting precipitate from alkaline solution

[0100] Next, the precipitate is collected from the alkaline solution.

[0101] As a method for collecting particles of the precipitate, for example, a method of filtering and washing with water can be cited. A method can be cited in which the precipitate (particles) is first taken out by filtering and then washed with water, and then the washed liquid is filtered to take out the precipitate (particles). Furthermore, the precipitate (particles) after washing with water can be further dried.

[0102] (6) A step of mixing the precipitate with a raw material containing Li to obtain a mixture

[0103] Then, if Figure 3 As shown in (c) in FIG. 1 , the collected precipitate (i.e., particles 20 containing hydroxide 2 of Ni, Co, and Mn generated around the core 4A of the additive) is mixed with the raw material 6 containing Li. For example, the collected precipitate particles and the raw material containing Li can be mixed in a mortar.

[0104] Examples of the raw material containing Li include Li 2 CO 3 , LiOH, and the like.

[0105] (7) Step of calcining the mixture

[0106] Next, the mixture of the collected precipitate (i.e., particles 20) and the raw material 6 containing Li is calcined. For example, the mixture can be calcined in a calcination furnace (muffle furnace, etc.). The calcination conditions can be, for example, a temperature of 800°C to 1100°C, an oxygen atmosphere, and a time of 5 hours to 20 hours.

[0107] In addition, it is preferred that after the above-mentioned calcination (hereinafter referred to as "first calcination"), calcination at a lower temperature (hereinafter referred to as "second calcination") is performed. For example, the particles that have undergone the first calcination can be crushed, a reducing agent (such as ascorbic acid) can be mixed with the crushed particles, and calcination can be performed using a calcination furnace (muffle furnace, etc.) at a temperature lower than that of the first calcination. The conditions for the second calcination can be, for example, a temperature of 400°C to 600°C, an oxygen atmosphere, and a time of 5 hours to 20 hours.

[0108] By calcining the mixture, Figure 3 As shown in (d) in the figure, the additive 4B diffuses inside the collected precipitate (i.e., the particle 20 containing the hydroxide 2 of Ni, Co and Mn is generated around the core 4A of the additive), and the additive element (M element) is fully dispersed in the inner region of the particle of the positive electrode active material. As a result, the M element partiality in the positive electrode active material can be controlled within the above range.

[0109] <Battery>

[0110] The battery according to the embodiment of the present disclosure has the positive electrode active material according to the embodiment of the present disclosure. The battery, for example, has a negative electrode, a positive electrode, a separator, and an electrolyte. The battery according to the embodiment of the present disclosure is preferably a liquid battery having a liquid electrolyte. In addition, it can be a solid battery having a solid electrolyte.

[0111] (Electrolyte)

[0112] The battery according to the embodiment of the present disclosure is preferably a liquid battery having an electrolyte solution.

[0113] Solvent

[0114] The electrolytic solution contains a solvent (non-aqueous solvent) and an electrolyte.

[0115] Examples of the solvent (non-aqueous solvent) include N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide (DEME), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI), and 1-ethyl-2,3-dimethylimidazolium bis(fluorosulfonyl)imide (DEMI-FSI).

[0116] Electrolytes

[0117] As the electrolyte in the electrolytic solution, for example, Li salts can be cited. As the Li salts, lithium bis(fluorosulfonyl)imide (LiFSI), LiPF6 (lithium hexafluorophosphate), lithium tetrafluoroborate (LiBF4), Li[N(CF3SO2)2], etc. can be cited.

[0118] The amount of the electrolyte may be, for example, 1.0 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.

[0119] The electrolyte may contain various additives, such as a thickener, a film-forming agent, a gas generator, etc., in addition to a solvent and an electrolyte. The electrolyte is typically a non-aqueous electrolyte that is liquid at room temperature (e.g., 25±10°C). The electrolyte is typically liquid in the battery usage environment (e.g., a temperature environment of -20 to +60°C).

[0120] (positive electrode)

[0121] As the positive electrode active material, there is the positive electrode active material according to the embodiment of the present disclosure. The details have been described above and are therefore omitted here.

[0122] As the conductive material, for example, carbon materials can be listed. The electrolyte can be a solid electrolyte or a liquid electrolyte. The solid electrolyte can be an organic solid electrolyte such as a gel electrolyte, or an inorganic solid electrolyte such as an oxide solid electrolyte or a sulfide solid electrolyte. In addition, the liquid electrolyte (electrolyte) contains, for example, a supporting salt such as LiPF6 and a solvent such as a carbonate solvent. In addition, as the adhesive, for example, a rubber adhesive and a fluoride adhesive can be listed.

[0123] In addition, as for the positive electrode, it is preferred that in addition to the positive electrode active material, a solid electrolyte selected from the solid electrolyte group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte is included, and more preferably at least a portion of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. As the halide solid electrolyte that covers at least a portion of the surface of the positive electrode active material, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5) [LTAF electrolyte].

[0124] The positive electrode current collector collects current from the positive electrode active material layer. Examples of the positive electrode current collector include stainless steel, aluminum, nickel, iron, titanium, carbon, etc., aluminum alloy foil or aluminum foil. Aluminum alloy foil and aluminum foil can be made using powder. The shape of the positive electrode current collector is, for example, foil-shaped or mesh-shaped.

[0125] (negative electrode)

[0126] The negative electrode active material layer contains at least a negative electrode active material. The negative electrode active material layer may further contain at least one of a conductive material, an electrolyte, and a binder. Examples of the negative electrode active material include metal active materials such as Li and Si, carbon active materials such as graphite, and Li4Ti5O 12 The negative electrode current collector may be in the form of a foil or a mesh. The conductive material, electrolyte, and binder are the same as those described above.

[0127] The electrolyte layer is disposed between the positive electrode active material layer and the negative electrode active material layer and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte. As the electrolyte layer, a solid electrolyte layer is preferred. The electrolyte layer may have a separator.

[0128] The negative electrode current collector collects current from the negative electrode active material layer. Examples of the material of the negative electrode current collector include metals such as copper, SUS, and nickel. Examples of the shape of the negative electrode current collector include foil and mesh.

[0129] (Solid-state battery)

[0130] As described above, the battery according to the embodiment of the present disclosure is preferably a liquid battery having a liquid electrolyte, but on the other hand, the battery according to the embodiment of the present disclosure may be a solid battery having a solid electrolyte. Therefore, the solid battery will be described below.

[0131] Solid electrolyte

[0132] The solid battery preferably contains, as a solid electrolyte, at least one solid electrolyte species selected from the solid electrolyte group consisting of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes.

[0133] As a sulfide solid electrolyte, it is preferred to contain sulfur (S) as the main component of the anion element, and it is more preferred to contain, for example, Li element, A element and S element. The A element is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In. The sulfide solid electrolyte may further contain at least one of O and a halogen element. As a halogen element (X), for example, F, Cl, Br, I and the like can be listed. There is no particular limitation on the composition of the sulfide solid electrolyte, for example, xLi2S·(100-x)P2S5(70≤x≤80), yLi I·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7≤x≤0.8, 0≤y≤30, 0≤z≤30) can be listed. The sulfide solid electrolyte may have a composition represented by the following general formula (1).

[0134] Li 4-x Ge 1-x P x S4(0<x<1)···Formula (1)

[0135] In formula (1), at least a portion of Ge may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In addition, at least a portion of P may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. A portion of Li may be replaced by at least one selected from Na, K, Mg, Ca and Zn. A portion of S may be replaced by a halogen. The halogen is at least one selected from F, Cl, Br and I.

[0136] As an oxide solid electrolyte, it is preferred to contain oxygen (O) as the main component of the anion element, for example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W and S), and O. As an oxide solid electrolyte, garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-PO-based solid electrolytes, Li-BO-based solid electrolytes, etc. can be listed. As a garnet-type solid electrolyte, for example, Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x ) 12 (0≤x≤2), Li5La3Nb2O 12 Etc. As perovskite-type solid electrolytes, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. can be cited. As NASICON-type solid electrolytes, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. can be cited. As Li-PO-based solid electrolytes, Li3PO4 and LIPON (compounds in which a part of O of Li3PO4 is replaced by N) can be cited. As Li-BO-based solid electrolytes, Li3BO3 and compounds in which a part of O of Li3BO3 is replaced by C can be cited.

[0137] As the halide solid electrolyte, a solid electrolyte containing Li, M and X is preferred (M represents at least one of Ti, Al and Y, and X represents F, Cl or Br). Specifically, Li 6-3z Y z X6 (X represents Cl or Br, z satisfies 0<z<2), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5). 6-3z Y z Among X6, Li3YX6 (X represents Cl or Br) is more preferred from the perspective of excellent lithium ion conductivity, and Li3YCl6 is further preferred. In addition, for example, from the perspective of suppressing oxidative decomposition of sulfide solid electrolytes, it is preferred to include Li3YX6 together with solid electrolytes such as sulfide solid electrolytes. 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5).

[0138] Solid battery structure

[0139] The structure of a solid battery has a stacked structure of positive electrode / solid electrolyte layer / negative electrode. The solid battery includes a so-called all-solid battery using a solid electrolyte as an electrolyte, and the solid electrolyte may contain less than 10% by mass of an electrolyte relative to the total amount of the electrolyte. Furthermore, the solid electrolyte may be a composite solid electrolyte comprising an inorganic solid electrolyte and a polymer electrolyte.

[0140] The positive electrode has a positive electrode active material layer and a current collector, and the negative electrode has a negative electrode active material layer and a current collector.

[0141] The solid electrolyte layer may have a single-layer structure or a multi-layer structure of two or more layers.

[0142] The solid battery may have a cross-sectional structure, for example, and the solid electrolyte layer may be a two-layer structure. The solid battery has: a negative electrode including a negative electrode collector and a negative electrode active material layer, a solid electrolyte layer, and a positive electrode including a positive electrode collector and a positive electrode active material layer. The negative electrode active material layer includes a negative electrode active material, a conductive auxiliary agent, and a binder. The positive electrode active material layer includes a coated positive electrode active material, a conductive auxiliary agent, and a binder. In the case of a coated positive electrode active material, the surface of the positive electrode active material is coated with an LTAF electrolyte or a LiNbO3 electrolyte.

[0143] In addition, the solid battery can be formed by sealing the stacked end faces (side faces) of the stacked structure of the positive electrode / solid electrolyte layer / negative electrode with a resin. The current collector of the electrode can be configured with a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer on the surface.

[0144] (Battery)

[0145] The laminated battery in the present disclosure is typically a lithium ion secondary battery. As the purpose of the battery, for example, a power source for a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), an electric vehicle (BEV), a gasoline vehicle, a diesel vehicle, etc. can be cited. It is particularly preferably used as a driving power source for a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV) or an electric vehicle (BEV). In addition, the battery in the present disclosure can be used as a power source for a mobile body (such as a railway, a ship, an aircraft) other than a vehicle, and can also be used as a power source for electrical products such as an information processing device.

[0146] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative only, and technical solutions having substantially the same configuration and having the same functions and effects as the technical ideas described in the patent claims in the present disclosure are all included in the technical scope of the present disclosure.

[0147] Example

[0148] The present disclosure will be described below based on examples, but the present disclosure is not limited to these examples.

[0149] <Example 1>

[0150] (Synthesis of positive electrode active material)

[0151] The method disclosed in the present invention is used to synthesize a x Ni a Co b Mn c M d A positive electrode active material having a composition represented by O2, x, a, b, c and d having the ratios shown in Table 1, and using the element described in Table 1 as the element represented by M.

[0152] · Raw material 1 solution

[0153] Al2(SO4)3 is dissolved in ion exchange water to obtain a solution of raw material 1. The concentration of the aqueous solution is adjusted to a range of 5 to 30% by mass.

[0154] ·Raw material 2 solution

[0155] NiSO4, CoSO4 and MnSO4 were dissolved in ion exchange water to obtain a solution of raw material 2. The ratio of Ni / Co / Mn was 1 / 1 / 1 (atm%), and the concentration of the aqueous solution was 30 mass%.

[0156] ·Crystallization

[0157] A certain amount of NH3 aqueous solution is placed in a reaction vessel, and nitrogen substitution is performed while stirring with a stirrer. NaOH is added to the reaction vessel to make the pH alkaline. Next, while controlling the pH in the reaction vessel to a certain pH (pH 10-12), the solution of raw material 1 is added dropwise to precipitate the hydroxide. Furthermore, while controlling the pH in the reaction vessel to a certain pH (pH 10-12), the solution of raw material 2 and NH3 are added dropwise to precipitate the transition metal hydroxide.

[0158] Washing, filtering, drying

[0159] The precipitated transition metal hydroxide is taken out by filtration, ion exchange water is added, stirred with a spoon to disperse it, and washed with water.

[0160] Next, the washed liquid is filtered to take out the transition metal hydroxide.

[0161] Next, the filtered transition metal hydroxide was dried at 120° C. for 16 hours to evaporate water.

[0162] ·Li raw material mixing

[0163] The dried transition metal hydroxide and Li2CO3 and LiOH as Li raw materials are mixed in a mortar.

[0164] ·Firing 1

[0165] The mixture of the transition metal hydroxide and the Li raw material is fired in a firing furnace (muffle furnace) at 800 to 1100° C. in an oxygen atmosphere for 10 hours.

[0166] ·Firing 2

[0167] The particles obtained in calcination 1 were crushed, mixed with ascorbic acid (reducing agent), and calcined in a calcination furnace (muffle furnace) at 400 to 600° C. in an oxygen atmosphere for 10 hours. In this way, the positive electrode active material of Example 1 was obtained.

[0168] <Examples 2 to 4>

[0169] The positive electrode active material of each example was obtained in the same manner as in Example 1, except that the additive used in the raw material 1 solution of Example 1 was changed from Al2(SO4)3 to BaSO4 (Example 2), Pr2(SO4)3 (Example 3) and La2(SO4)3 (Example 4).

[0170] <Comparative Example 1>

[0171] (Synthesis of positive electrode active material)

[0172] Synthesis of Li x Ni a Co b Mn c The composition represented by O2 and the ratios of x, a, b and c are shown in Table 1 for the positive electrode active material.

[0173] ·Raw material 2 solution

[0174] NiSO4, CoSO4 and MnSO4 were dissolved in ion exchange water to obtain a solution of raw material 2. The ratio of Ni / Co / Mn was 1 / 1 / 1 (atm%), and the concentration of the aqueous solution was 30 mass%.

[0175] ·Crystallization

[0176] A certain amount of NH3 aqueous solution is placed in a reaction container and nitrogen is replaced while stirring with a stirrer. NaOH is added to the reaction container to make the pH alkaline. Next, while controlling the pH in the reaction container to a certain pH (pH 10-12), the solution of raw material 2 and NH3 are added dropwise to precipitate the transition metal hydroxide.

[0177] Washing, filtering, drying

[0178] The precipitated transition metal hydroxide is taken out by filtration, ion exchange water is added, stirred with a spoon to disperse it, and washed with water.

[0179] Next, the washed liquid is filtered to take out the transition metal hydroxide.

[0180] Next, the filtered transition metal hydroxide was dried at 120° C. for 16 hours to evaporate water.

[0181] ·Li raw material mixing

[0182] The dried transition metal hydroxide and Li2CO3 and LiOH as Li raw materials are mixed in a mortar.

[0183] ·Firing 1

[0184] The mixture of the transition metal hydroxide and the Li raw material is fired in a firing furnace (muffle furnace) at 800 to 1100° C. in an oxygen atmosphere for 10 hours.

[0185] ·Firing 2

[0186] The particles obtained in calcination 1 were crushed, mixed with ascorbic acid (reducing agent), and calcined in a calcination furnace (muffle furnace) at 400 to 600° C. in an oxygen atmosphere for 10 hours. In this way, the positive electrode active material of Comparative Example 1 was obtained.

[0187] <Comparative Example 2>

[0188] (Synthesis of positive electrode active material)

[0189] The conventional method was used to synthesize a Li x Ni a Co b Mn c M d A positive electrode active material having a composition represented by O2, x, a, b, c and d having the ratios shown in Table 1, and using the element described in Table 1 as the element represented by M.

[0190] ·Raw material 2 solution

[0191] NiSO4, CoSO4 and MnSO4 were dissolved in ion exchange water to obtain a solution of raw material 2. The ratio of Ni / Co / Mn was 1 / 1 / 1 (atm%), and the concentration of the aqueous solution was 30 mass%.

[0192] ·Crystallization

[0193] A certain amount of NH3 aqueous solution is placed in a reaction container and nitrogen is replaced while stirring with a stirrer. NaOH is added to the reaction container to make the pH alkaline. Next, while controlling the pH in the reaction container to a certain pH (pH 10-12), the solution of raw material 2 and NH3 are added dropwise to precipitate the transition metal hydroxide.

[0194] Washing, filtering, drying

[0195] The precipitated transition metal hydroxide is taken out by filtration, ion exchange water is added, stirred with a spoon to disperse it, and washed with water.

[0196] Next, the washed liquid is filtered to take out the transition metal hydroxide.

[0197] Next, the filtered transition metal hydroxide was dried at 120° C. for 16 hours to evaporate water.

[0198] Mixing of Li raw materials and additive elements

[0199] Dried transition metal hydroxide, Li 2 CO 3 and LiOH as Li raw materials, and Ta(SO 4 ) 2 as a compound containing an additive element (M element=Ta) are mixed in a mortar.

[0200] ·Firing 1

[0201] The mixture of the transition metal hydroxide and the Li raw material is fired in a firing furnace (muffle furnace) at 800 to 1100° C. in an oxygen atmosphere for 10 hours.

[0202] ·Firing 2

[0203] The particles obtained in calcination 1 were crushed, mixed with ascorbic acid (reducing agent), and calcined in a calcination furnace (muffle furnace) at 400 to 600° C. in an oxygen atmosphere for 10 hours. In this way, the positive electrode active material of Comparative Example 2 was obtained.

[0204] [Determination of the bias rate of M element]

[0205] TEM-EDX images of cross sections of the particles of the positive electrode active materials obtained in Examples 1 to 4 and Comparative Example 2 were taken. A schematic diagram of the cross section image is shown in FIG. Figure 1 . Figure 1 The positive electrode active material particle 2 shown contains particles 4B of the element M inside. In the cross-sectional image of the positive electrode active material particle 2, the inner region from the center to 70% of the radius (i.e., the region from the surface to 30% of the radius is excluded) is shown. Figure 1 The inner area surrounded by the dotted line in the figure is taken as the observation object. Figure 2The area shown is divided into 10 nm square regions, and the concentration of the M element is measured for each region.

[0206] However, there are regions in the 10 nm square area at the end of the inner region that are not filled with positive electrode active material particles 2. Therefore, only the regions in the 10 nm square area that are entirely filled with positive electrode active material particles 2 are measured.

[0207] Then, the ratio of regions where the concentration of the M element is 10 mass % or more in all regions divided into 10 nm squares (excluding regions not filled with positive electrode active material particles 2) is calculated. This ratio is calculated according to the following formula.

[0208] The ratio = the number of regions where the concentration of the M element is 10 mass % or more / the number of all regions divided into 10 nm squares in the inner region (excluding regions not filled with positive electrode active material particles) × 100

[0209] This ratio calculation was performed on 10 cross-sectional images of particles of the positive electrode active material, and the arithmetic mean value was defined as the M element partial ratio.

[0210] [Production of battery cells]

[0211] A battery cell was produced using the positive electrode active material obtained in each of the Examples and Comparative Examples.

[0212] Battery cell structure

[0213] Winding cylinder

[0214] Positive electrode composition: Positive electrode active material / acetylene black (conductive material) / polyvinylidene fluoride = 88 / 10 / 2 (mass %)

[0215] Negative electrode composition: natural graphite / styrene butadiene rubber (SBR) / carboxymethyl cellulose (CMC)

[0216] Electrolyte composition: electrolyte = LiPF6 (1M), solvent = ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) = 3 / 4 / 3 (volume %)

[0217] Electrode production

[0218] The positive electrode and the negative electrode were coated on the current collector using a coater with a film thickness adjustment function (manufactured by Ohlgod Co., Ltd.), and dried at 80° C. for 5 minutes using a dryer to produce a battery cell.

[0219] [Determination of resistance increase rate after cycling]

[0220] For the battery cells obtained in each embodiment and comparative example, the battery resistance was measured before and after the cycle under the following test conditions. The results of the ratio of the battery resistance after the cycle (resistance increase rate (%)) when the battery resistance before the cycle is set to "100%" are shown in Table 1. The closer the resistance increase rate is to 100%, the better the battery characteristics can be said to be.

[0221] Test conditions: 300 cycles of charge and discharge at 60°C and 2C rate between SOC 0% and 100%.

[0222] [Table 1]

[0223]

[0224] As shown in Table 1, it can be seen that in Examples 1 to 4 where the M element partiality is 1.0% or more, the resistance increase rate after cycling can be reduced compared with Comparative Example 2 where the M element partiality is less than 1.0% and Comparative Example 1 containing no added element (M element).

Claims

1. The positive electrode active material has Li x Ni a Co b Mn c M d O2 represents a composition, for the TEM-EDX image of the cross section of the particle of the positive electrode active material, when the inner area from the center of the particle to 70% of the radius is divided into 10nm square areas, the proportion of the area in which the concentration of the element represented by M is 10 mass% or more is 1.0% or more relative to the whole area, and in the composition, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, a+b+c=1.0, 0.0005≤d≤0.05, and M represents at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh and Zr.

2. The positive electrode active material according to claim 1, wherein The element represented by the M is at least one element selected from Ta, Al, Ba, Pr, and La.

3. The positive electrode active material according to claim 2, wherein The element represented by the M is La.

4. The positive electrode active material according to claim 1, wherein The ratio of the region in which the concentration of the element represented by M is 10 mass % or more is 3.0% or more with respect to the entire region. 5 . A battery comprising the positive electrode active material according to claim 1 .

6. A method for producing a positive electrode active material, comprising: A step of preparing a solution A in which a raw material containing an element represented by M is dissolved; A step of preparing a solution B in which raw materials respectively containing Ni, Co and Mn are dissolved; A step of adding the solution A to an alkaline solution to precipitate hydroxide; A step of adding the solution B to the alkaline solution in which the hydroxide is precipitated to cause precipitation; A step of collecting a precipitate from the alkaline solution; a step of mixing the precipitate with a raw material containing Li to obtain a mixture; and The step of calcining the mixture, Wherein, M represents at least one element selected from Ta, Al, Ba, Pr, La, Y, Sr, Ce, Se, Hf, Rh and Zr.

Citation Information

Patent Citations

  • Screen device

    JP1988059323A

  • Transition metal composite hydroxide particle, manufacturing method of transition metal composite hydroxide particle, positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery

    JP2021147314A